2003
DOI: 10.1007/bf02287426
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between school characteristics and the availability of mental health and related health services in middle and high schools in the United States

Abstract: Problems related to mental illness are increasingly becoming the focal point of public concern over the safety and performance of schools, yet little is known about the availability and quality of school-based mental health services in the United States. In this article it is estimated that approximately 50% of US middle and high schools have any mental health counseling services available onsite and approximately 11% have mental health counseling, physical examinations, and substance abuse counseling availabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
33
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(36 citation statements)
references
References 29 publications
3
33
0
Order By: Relevance
“…Although similar rates of ASD prevalence are reported in both rural (0.9%) and urban (1.0%) areas (Mohamed et al, 2016), individuals in rural communities, report limited access to the types of resources required for timely and appropriate identification and intervention services (Cohen and Hesselbart, 1993; Slade, 2003; Green et al, 2013; Gona et al, 2016). There are specific factors which contribute to barriers in diagnosis and services for affected individuals and families in rural settings.…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…Although similar rates of ASD prevalence are reported in both rural (0.9%) and urban (1.0%) areas (Mohamed et al, 2016), individuals in rural communities, report limited access to the types of resources required for timely and appropriate identification and intervention services (Cohen and Hesselbart, 1993; Slade, 2003; Green et al, 2013; Gona et al, 2016). There are specific factors which contribute to barriers in diagnosis and services for affected individuals and families in rural settings.…”
Section: Introductionmentioning
confidence: 78%
“…In general, poor availability and implementation of mental health services for children has been reported for rural areas (Cohen and Hesselbart, 1993; Slade, 2003; Green et al, 2013; Cummings et al, 2015), however, there is little research examining the specific barriers that prevent children with ASD and their families from benefitting fully from services available in rural settings. In this section, we outline recently identified barriers to implementation, and we suggest specific solutions that may increase the availability of effective screening and intervention strategies.…”
Section: Implementation Of Asd Services In Rural Settingsmentioning
confidence: 99%
“…[39][40][41][42] A number of studies have found that children in rural areas have less access to regular and specialty care. 43,44 It may also be that a critical mass of children with ASD, which is more likely found in densely populated areas, may increase physicians' and families' familiarity with the disorder.…”
Section: Discussionmentioning
confidence: 99%
“…6 Public schools have become the main provider of behavioral health services to children in the United States (US) and are responsible for approximately 70–80% of all behavioral health services delivered to children. 1114 Schools provide convenient access to behavioral health services and significantly reduce barriers to treatment seen in traditional outpatient settings, particularly in ethnic minority groups 1517 …”
mentioning
confidence: 99%